Effect of carbon on mechanical properties of Fe-23 wt% Al alloy - Baligidad R.G.; Radhakrishna A.; Sarma D.S. (My University, 2025)
The effect of carbon addition on the mechanical properties of Fe-23 wt% Al alloy was investigated. About 35 kg melts of iron aluminides based on FeAl with the compositions, Fe-23Al-0.27C and Fe-23Al-1.3C were prepared by a combination of air induction-melting with flux cover (AIMFC) and electroslag remelting ESR). A small amount of carbon addition to binary Fe-23Al alloy has resulted in improved tensile strength, creep properties and machinability. Increases in carbon content from 0.27 to 1.3 wt% produced further improvement in machinability but resulted in poor tensile strength and creep properties.